Thermal comfort in an adobe room with heat storage system in the Andes of Peru - Holguino Huarza, Antonio (2018)
The objective of this work was the evaluation of thermal comfort inside the test room (HP), of adobe and materials of the high Andean area of Peru, like the andesite stone that is a heat accumulator. This experimental research work determined the values of thermal conductivity 0,176  0,149 and 0,118 W / mK for the adobe, plaster and straw. It was made a comparison was made between the values of thermal conductivity and specific heat, obtained experimentally for the materials and systems used in the construction of HP with the known values of specific materials such as water and air. The design and use of the materials in the construction of the wall, door and window, allowed to determine the values of the thermal conductivities equal to 0,061  0,030 and 0,027 W / mK respectively, that are similar to the thermal conductivity of a natural thermal insulator such as air whose value is 0.026 W / mK. The transfer of heat energy to the outside of the HP, during 11 hours at night is 0,815 MJ. The energy accumulator installed in the HP built with stone, guano and wood whose specific heat values were 1235,13  2416,44 and 2212,77 J / kgK respectively compared with the water, that is a good energy storage, that represent 29,55  57,81 and 52,94% respectively. The HP storage system stores heat energy equivalent to 8,305 MJ, the surplus of heat energy allows that temperature inside HP during the winter times to have average values higher in 63, 83 and 68, 83% at the average temperatures of HC and MAC respectively.